Inorganic nanocrystals as contrast agents in MRI: synthesis, coating and introduction of multifunctionality. (10th January 2013) - Cormode, David P.; Sanchez‐Gaytan, Brenda L.; Mieszawska, Aneta J.; Fayad, Zahi A.; Mulder, Willem J. M.; Mulder, Willem J. M.; McMahon, Michael T.; Nicolay, Klaas
<x xml:space="preserve">Abstract</x> Inorganic nanocrystals have myriad applications in medicine, including their use as drug or gene delivery complexes, therapeutic hyperthermia agents, in diagnostic systems and as contrast agents in a wide range of medical imaging techniques. In MRI, nanocrystals can produce contrast themselves, with iron oxides having been the most extensively explored, or can be given a coating that generates MR contrast, for example gold nanoparticles coated with gadolinium chelates. These MR‐active nanocrystals can be used for imaging of the vasculature, liver and other organs, as well as molecular imaging, cell tracking and theranostics. As a result of these exciting applications, the synthesis and rendering of these nanocrystals as water soluble and biocompatible are therefore highly desirable. We discuss aqueous phase and organic phase methods for the synthesis of inorganic nanocrystals, such as gold, iron oxides and quantum dots. The pros and cons of the various methods are highlighted. We explore various methods for making nanocrystals biocompatible, i.e. direct synthesis of nanocrystals coated with biocompatible coatings, ligand substitution, amphiphile coating and embedding in carrier matrices that can be made biocompatible. Various examples are highlighted and their applications explained. These examples signify that the synthesis of biocompatible nanocrystals with controlled properties has been achieved by numerous research groups and can be applied to a wide range of applications. Therefore, we expect to see reports of preclinical applications of ever more complex MRI‐active nanoparticles and their wider exploitation, as well as in novel clinical settings. Copyright © 2013 John Wiley & Sons, Ltd.